MDMA, methamphetamine, and CYP2D6 pharmacogenetics: what is clinically relevant? - De La Torre, Rafael; Yubero-Lahoz, Samanta; Pardo-Lozano, Ricardo; Farre, Magi (Frontiers in Genetics, 2012)
In vitro human studies show that the metabolism of most amphetamine-like psychostimulants is regulated by the polymorphic cytochrome P450 isozyme CYP2D6. Two compounds, methamphetamine and 3,4-methylenedioxymethamphetamine (MDMA), were selected as archetypes to discuss the translation and clinical significance of in vitro to in vivo findings. Both compounds were chosen based on their differential interaction with CYP2D6 and their high abuse prevalence in society. Methamphetamine behaves as both a weak substrate and competitive inhibitor of CYP2D6, while MDMA acts as a high affinity substrate and potent mechanism-based inhibitor (MBI) of the enzyme. The MBI behavior of MDMA on CYP2D6 implies that subjects, irrespective of their genotype/phenotype, are phenocopied to the poor metabolizer phenotype. The fraction of metabolic clearance regulated by CYP2D6 for both drugs is substantially lower than expected from in vitro studies. Other isoenzymes of cytochrome P450 and a relevant contribution of renal excretion play a part in their clearance. These facts tune down the potential contribution of CYP2D6 polymorphism in the clinical outcomes of both substances. Globally, the clinical relevance of CYP2D6 polymorphism is lower than that predicted by in vitro studies.